A Brief Overview of Cancer Vaccines. Issue 1 (January 2023) - Muller, Alexander J.; Thomas, Sunil; Prendergast, George C.
Abstract: Vaccine strategies for cancer differ from infectious disease in focusing mainly on clearing rather than preventing disease. Here we survey general vaccine strategies and combination therapy concepts being investigated for cancer treatment, with a focus on tumor antigens rather than cancer-inducing viruses or microorganisms. Many tumor antigens are "altered-self" and tend to arouse weaker immune responses than "foreign" antigens expressed by infectious agents. Further, unlike an infectious disease patient, a cancer patient's immune system is damaged, suppressed, or senescent and mainly tolerant of their disease. Thus, vaccine efficacy in a cancer patient will rely upon adjuvant or combination treatments that correct the inflammatory tumor microenvironment and degrade tumoral immunosuppression that dominates patient immunity. This brief overview is aimed at new researchers in cancer immunology seeking an overview of vaccine concepts to eradicate malignancy by provoking a selective immune attack.